Affects in virtual context of Telematic Engineering at Universidad Centroccidental Lisandro Alvarado (Dissertare, 2016)
This paper, still in progress, is devoted to propose theoretical elements to support the inclusion of affective attitude inTelematic Engineering virtual environments at UCLA, as epistemological aspect of a reality from qualitative study. This research has an interpretative methodology that can guide teachers regarding the management of their emotions in virtual environments. This study is based on interviews and non-participant observation as data collection techniques. The participants are teachers from Telematic Engineering (first semester) during academic term 2016-1. The results of this paper will provide new elements to deepen analysis of theoretical approach of Emotions for Educational Virtual Environments in bimodal way. As preliminary finding of this research, it is asserted the presence of affective elements on virtual environments from Telematic Engineering at UCLA in order to include attitudes that involve a series of affective demonstrations through language, resources, activities and events which show interest by participants from their teachers. As result, the affective elements from Telematic Engineering virtual environments at UCLA were expressed through the following aspects: language, attitude, structure of the course and resources (Varela, 2014). These approaches represent the beginning to generate reflections about how to find the way to improve the empathy between teachers and students in virtual environments to optimize learning processes.
Keywords: affective attitude; entornos virtuales; learning